2023
DOI: 10.3390/app13127324
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Adsorption of Single-Stranded and Double-Stranded DNA on the Surface of Gold Nanoparticles

Abstract: Understanding the patterns of noncovalent adsorption of double-stranded nucleic acids (dsDNA) on gold nanoparticles (GNPs) was the aim of this study. It was found that the high-affinity motifs in DNA can and do act as an “anchor” for the fixation of the whole molecule on the GNP (up to 98 ± 2 single-stranded (ss)DNA molecules per particle with diameter of 13 ± 2 nm). At the same time, the involvement of an “anchor” in the intramolecular DNA interaction can negatively affect the efficiency of the formation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…Next, the incubations of the sensor with 1 nM, 10 nM, 50 nM, and 100 nM DNA targets determined successive increases in current intensity, which can be explained by the formation of dsDNA with each addition of a DNA target. In agreement with the previous findings [ 31 ], we may assume that the newly formed dsDNA easily detaches from the surface, thus favoring the redox process of [Fe(CN) 6 ] 3–/4– species. The impedimetric measurements ( Figure 9 B) were in agreement with the CV results and showed an increase in Rct following the adsorption of the DNA probe at the AuNPs-RGO/SPCE interface, which impeded the redox process of the negatively charged [Fe(CN) 6 ] 3–/4– .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Next, the incubations of the sensor with 1 nM, 10 nM, 50 nM, and 100 nM DNA targets determined successive increases in current intensity, which can be explained by the formation of dsDNA with each addition of a DNA target. In agreement with the previous findings [ 31 ], we may assume that the newly formed dsDNA easily detaches from the surface, thus favoring the redox process of [Fe(CN) 6 ] 3–/4– species. The impedimetric measurements ( Figure 9 B) were in agreement with the CV results and showed an increase in Rct following the adsorption of the DNA probe at the AuNPs-RGO/SPCE interface, which impeded the redox process of the negatively charged [Fe(CN) 6 ] 3–/4– .…”
Section: Resultssupporting
confidence: 92%
“…Among these, the electrochemical synthesis of Au nanostructures has been widely employed because it offers several advantages over chemical synthesis, including the ability to control the size, shape, morphology, and growth rate by modulating the applied potential or current and via the electrolyte concentration [ 27 , 28 , 29 ]. Several studies have demonstrated that single-stranded (ss) oligonucleotides possess a more pronounced affinity for gold nanoparticles than their corresponding double-stranded (ds) helix [ 30 , 31 ]. Li and Rothberg mentioned that the underlying adsorption mechanism of ssDNA on gold is electrostatic and exploited the difference in the electrostatic properties of ssDNA and dsDNA in DNA detection by a colorimetric assay [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Next, the incubations of the sensor with 1 nM, 10 nM, 50 nM, and 100 nM DNA targets determined successive increases in current intensity, which can be explained by the formation of dsDNA with each addition of a DNA target. In agreement with the previous findings [31], we may assume that the newly formed dsDNA easily detaches from the surface, thus favoring the redox process of [Fe(CN) 6 ] 3-/4species. The impedimetric measurements (Figure 9B) were in agreement with the CV results and showed an increase in Rct following the adsorption of the DNA probe at the AuNPs-RGO/SPCE interface, which impeded the redox process of the negatively charged [Fe(CN) 6 ] 3-/4-.…”
Section: Structural Characterizationsupporting
confidence: 92%
“…ssDNA forms multipoint contacts with AuNP, and the nucleotide sequence, its length, the presence of modifications in DNA, the ionic strength and pH of the medium during incubation, the temperature, and reaction time of the association significantly affect the efficiency of the observed adsorption of cDNA to the surface of AuNP. It is shown that the adsorption of various DNA structures (dsDNA, ssDNA with a hairpin structure, and self-complementary ssDNA) on AuNP really differs significantly from nanoparticles [132].…”
Section: Dna Adsorption Over the Nanoparticlesmentioning
confidence: 99%
“…According to a number of studies, it is this interaction that determines the binding strength of NA with AuNP. The second difference is that ssDNA has a much more mobile structure, whereas dsDNA has a rigid structure that prevents direct interaction of nitrogenous bases with the surface of nanoparticles [132].…”
Section: Dna Adsorption Over the Nanoparticlesmentioning
confidence: 99%